Onomastics of Aleksinac’s Village of Korman - Stefanović, Dušan R. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper presents the onomastic material from Korman, a village located in the northwestern part of Pomoravlje of Aleksinac. After some remarks about the village itself, the paper contains a list of microtoponyms as well as a list of anthroponyms, including surnames, male personal names, female personal names, male nicknames, female nicknames, male hypocoristics and female hypocoristics. The main reason for extracting the onomastic material from Korman is that it has not yet been presented to the scientific public and the material presented in this paper will serve for future broader onomastic research.